Aplikasi Perbedaan Waktu Pemberian Pakan Berhormon Terhadap Sex Reversal Pada Ikan Mas Sinyonya (Cyprinus carpio L.) G2N F1 - Dodi Hermawan; Rinda Ismalasari; Saifullah Saifullah; Adi Sucipto; Lukman Anugrah Agung (Jurnal Akuakultur Sungai dan Danau, 2023)
This study was conducted to determine the best duration of hormone addition through the feed to induce the sex ratio of common carp strain Sinyonya. The study was using a completely randomized design with 5 different treatments namely A (control), B (30 days), C (35 days), D (40 days), and E (45 days) and each performed in 3 replications. The fish samples used in this study were a common carp strain Sinyonya larvae 5 days after hatching and still have the egg yolks. A total of 1.500 larvae of fish larvae were used. The fish larvae were given feed that had been mixed with 17a-methyltestosteron hormone. Feed was provided ad hormonal satiation at 5 times a day, (08.00, 10.00, 12.00, 14.00 and 16.00). The average percentage of the male fish with the highest value obtained in treatment C (35 days) is equal to 100.00±0.00. The result showed that the addition of 17a-methyltestosterone hormone on feed for 35 days and 40 days was the best treatment to improve the sex ratio of male of common carp strain Sinyonya.